¿What is humanism? A brief understanding in the long run. - Álvarez Pitaluga, Antonio (2023)
The article proposes a brief panoramic and historical tour, through important milestones in universal history, on the emergence and general developmentof humanism as a theoretical and methodological conception for the study and understanding of social reality. This trajectory is proposed accordingto the personal criteria of the author. The fundamental idea that it aspires to demonstrate starts from the fact that humanism is above all an interpretive model of social reality in search of the improvement of human beings and their societies.